BECOMING ROBERTO BOLAÑO: A SURVEY OF POETIC CONGENIALITY AND THE “PERFORMING AUTHORSHIP” OF PATTI SMITH - Bolte, Rike (Revista Chilena de Literatura, 2023)
In this essay, a marginal and —at the same time— prominent phenomenon in the exegesis of Roberto Bolaño’s work is studied: the performance offered by the rock-veteran Patti Smith, as reader of the Chilean author, in an interview that took place in Madrid, in 2010. Smith meta-positions herself with respect to the “literary system”, but she also uses a concept inherited from romanticism, the poetic congeniality, locating herself in an inter-authorial dimension with Bolaño. Then, she performs several nostalgic exercises: the (re)staging of her own poetic authorship, and the projection of her authorial presence as a singer on/from Bolaño’s absence. These interventions by Smith are analyzed in relation to a study by Sonja Longolius dedicated to the “performing authorship”, which at the same time takes up the Deleuze and Guattari’s theory of becoming author, and the transmission of the great texts (of cult).